Cigarette Addiction as The Gateway to Drug Addiction - Ali Johardi Wirogioto (International Journal of Social Service and Research, 2022)
Smoking is not a cultural heritage of the Indonesian nation. Smoking is a habit that begins in adolescence. WHO data confirms that adolescents have a high tendency to smoke. Initially, smokers were under the age of 18, around 7.2 percent in 2013 and increased to 9.1 percent in 2018. Teenage students are more likely to smoke than adults. It is believed that 1 in 4 drug addicts started as addicted to cigarettes. In contrast, 90 percent of them started being addicted to drugs when they were 18. Because the brain is still developing until the age of 25, if, at that time, the brain was familiar with nicotine, cigarettes would be a gateway to addiction to other compounds, especially alcohol and illegal drugs. This qualitative descriptive study aims to determine what causes cigarette addicts to become drug addicts. The study results show that many factors cause a common thread between cigarette addicts and drug addicts, starting with the desire to try, pressure from peer groups or peer groups, being trapped and eventually falling into drug abuse. The low price during the massive promotion of cigarettes by sponsoring various school activities is considered a supporting factor.